Diagnosis Molekuler Virus Flu Burung-A Subtipe H5 Berdasarkan Amplifikasi Gen M dan H5 dengan Metode Onestep Simplex RT-PCR (MOLECULAR DIAGNOSIS OF AVIAN INFLUENZA VIRUS TYPE A AND SUBTYPE H5 BY AMPLIFICATION OF ITS M AND H5 GENES USING ONE STEP SIMPLEX R - Haryanto, Aris; Krisanti, Bibiana; Irianingsih, Sri Handayani; Yudianingtyas, Dini Wahyu (Jurnal Veteriner, 2013)
Influenza A viruses which belong to the Family of Orthomyxoviridae are a group of viruses withsegmented ssRNA genome. The viruses can be subgroupped into many subtypes on the basis of theirsurface glycoproteins, hemagglutinin (HA) and neuraminidase (NA) proteins. Among the HA subtypes, H5and H7 have been found to be the most pathogenic. Conventional diagnosis of the viruses is usuallyperformed by isolation of the viruses in embryonated eggs, and hemagglutination (HA) and hemagglutinationinhibition test. Although those methods are sensitive and accurate, they are time consuming and requirelaboratory facilities with high biosafety level. Commercial methods such as emzyme-linked immonosorbentassay (ELISA) and immunoflurescense assay also provide a rapid result but less sensitive and specificthan conventional methods. Molecular diagnosis by amplification of M and H5 genes using one strepsimplex reverse transcriptase-polymerase chain eraction (RT-PCR) provices a rapid and accurate diagnosisfor the viruses. A study was therefore conducted to evaluate the accurate and rapidity of such the moleculartests for diagnosis of avian influenza A virus, subtype H5. As many as 10 sample of the virus isolateswhich were available at the Animal Desease investigation Center in Wates, Yogyakarta, were uses in thisstudy. The virus isolates were firstly propagated in specific antigen negative (SAN) chicken embryos andtested by HA/HI test. The viruses were then subjected for the RT-PCR test with varying annealingtemperatures of 500C and 520C. The result showed that all 10 isolates were type A influenza virus and 8out of 10 were influenza A subtype H5 influenza virus. RT-PCR used in this study appears to be moresensitive, rapid and accurate as compared to those by serological and isolation of the virus in embryonatedeggs.
Keywords: AI virus, HA and HI test, M and H5 genes, OneStep Simplex RT-PCR